Elaboración y estandarización de microencapsulados de aceites esenciales de hierba luisa (Cymbopogon citratus) y hojas de ishpink (Ocotea quixos) como aditivos nutricionales para piscicultura - Caicedo de la Cruz, Diego Javier (2016)
The research was conducted in the laboratories of Centro de Investigación y Valoración de la Biodiversidad CIVABI of Universidad Politécnica Salesiana which consisted of microencapsulating essential oils of Lemon grass (Cymbopogon citratus) and Ishpink (Ocotea quixos) under the technic of ionic gels for a future application in pisciculture, as a supplement in pet food diets. The essential oils obtained from “Fundación Chankuap” located in the city of Macas, province of Morona Santiago were used as the active ingredient to produce microcapsules through emulsions based on sodium alginate, glycerin and Tween 80 at different concentrations (2: 1 and 3: 1 ) in contact with a calcium chloride solution, plus a gum arabic coating. Through GC-MS analysis of the essential oils performed at the beginning of the research, detailed information of their chemical composition was obtained, and when compared with microencapsulated stored for three weeks it allowed to verify the conservation of the active ingredient at the end of the process in environmental conditions. The homemade system developed under laboratory conditions allowed to obtain microcapsules with a hemispherical shape, a diameter no bigger than 800 µm in wet capsules and 700 µm in dry capsules. Also the encapsulation efficiency was 70% in samples with Ishpink (2: 1 and 3: 1) and the production yield of 80% and a percentage of active compound encapsulation of 45% in concentrations 2:1 of Lemon grass and Ishpink.